2019
DOI: 10.1155/2019/1808419
|View full text |Cite
|
Sign up to set email alerts
|

Granule of BU-XIN RUAN-MAI Attenuates the Patients’ Angina Pectoris of Coronary Heart Disease via Regulating miR-542-3p/GABARAP Signaling

Abstract: Objective. Coronary heart disease (CHD) has been regarded as a serious and common disease in the modern society. This study aims to investigate the effect of Granule of BU-XIN RUAN-MAI (BXRM) on angina pectoris of coronary heart disease and to explore the molecular mechanisms underlying Granule of BU-XIN RUAN-MAI-mediated protective activity against this disease. Methods. The effects of Granule of BU-XIN RUAN-MAI on clinical symptoms of patients’ angina were indicated by hemorheology indicators including high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Subsequently, expression of candidate miRNAs in footpads of mice after MSU treatment was detected, and the results disclosed that miR-542-3p expression was decreased in footpads of GA mice. Previously, miR-542-3p was proposed to regulate the inflammatory response in cerebral injury [ 38 ], coronary heart disease [ 39 ], and respiratory viral infections [ 40 ]. In the present study, we found that SNHG8 binds with miR-542-3p and negatively regulates its expression in THP-1-derived macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, expression of candidate miRNAs in footpads of mice after MSU treatment was detected, and the results disclosed that miR-542-3p expression was decreased in footpads of GA mice. Previously, miR-542-3p was proposed to regulate the inflammatory response in cerebral injury [ 38 ], coronary heart disease [ 39 ], and respiratory viral infections [ 40 ]. In the present study, we found that SNHG8 binds with miR-542-3p and negatively regulates its expression in THP-1-derived macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The haemodynamic change caused by early coronary artery disease or atherosclerosis is the basic mechanism of SAP [11], which is similar to the perspective of traditional Chinese medicine (TCM) [12]. TCM has been used in China for more than 2000 years and plays a significant role in the treatment of SAP.…”
Section: Background and Rationale {6a}mentioning
confidence: 78%
“…miR-542-3p functioned in regulating antiviral and inflammatory responses [16] . Buxin Ruanmai granules could repress the inflammatory reaction and oxidative stress of myocardial cells through the miR-542-3p/GABARAP axis [17] . All the results indicated the implication of miR-542-3p in CAP.…”
Section: Resultsmentioning
confidence: 99%